Analytic Solution of Steady Three-Dimensional Problem of Condensation Film on Inclined Rotating Disk by Differential Transform Method. (9th August 2010) - Rashidi, Mohammad Mehdi; Mohimanian pour, Seyyed Amin
Abstract : The differential transform method (DTM) is applied to the steady three-dimensional problem of a condensation film on an inclined rotating disk. With similarity method, the governing equations can be reduced to a system of nonlinear ordinary differential equations. The approximate solutions of these equations are obtained in the form of series with easily computable terms. The velocity and temperature profiles are shown and the influence of Prandtl number on the temperature profiles is discussed in detail. The validity of our solutions is verified by the numerical results.